SARS-CoV-2: Emergence of New Variants and Effectiveness of Vaccines - Singh, Desh Deepak; Parveen, Amna; Yadav, Dharmendra Kumar (Frontiers in Cellular and Infection Microbiology, 2021)
The advent of SARS-CoV-2 variants may cause resistance at the immunity level against current vaccines. Some emergent new variants have increased transmissibility, infectivity, hospitalization, and mortality. Since the administration of the first SARS-CoV-2 vaccine to the human in March 2020, there is going on a global race against SARS-CoV-2 to control the current pandemic situation. Spike (S) glycoprotein of SARS-CoV-2 is the main target for current vaccine development, which can neutralize the infection. Companies and academic institutions have developed vaccines based on the S glycoprotein, as well as its antigenic domains and epitopes, which have been proven effective in generating neutralizing antibodies. The effectiveness of SARS-CoV-2 vaccines and other therapeutics developments are trapped up by the new emergent variants at the global level. We have discussed the emergence variants of SARS-CoV-2 on the efficacy of the developed vaccine. Presently, most of the vaccines have been tremendously effective in severe diseases.However, there are still noteworthy challenges in certifying impartial vaccines, the story of re-infections is generating a more stressful condition, and this needs further clinical evaluation.